"Place Making" and "Place Attachment" as Key Concepts in Understanding and Confronting Contemporary Urban Evictions: The Case of Givat-Amal, Tel Aviv. (December 2022) - Bigon, Liora; Bitton, Yifat; Langenthal, Edna
This article expands on the usability of the concepts of "place making" and "place attachment" as recently developed in urban studies research in the context of housing insecurity of marginalized communities in today's neo-liberal city. Particularly, against the growing threat of urban evictions, the article utilizes a transdisciplinary approach, showing the relevance of both concepts for (a) a better understanding of bottom-up processes of spatial production and attempts to create a sense of place on the part of such communities, and (b) offering an innovative legal strategy for doing justice to these communities in terms of their compensation rights, especially where a title to land has not been registered on a private basis. These issues are critically examined on the site-related case of the Givat-Amal quarter in Tel Aviv, Israel. This district is now under actual final threat of forced evictions following seven conflicted decades with the state, municipal authorities and private entrepreneurs. Our transdisciplinary study is based on qualitative methodologies in human geography such as fieldwork, visual evidence, and interviews, with a glimpse into philosophy. It is equally based on revisiting "traditional" legal property rights through the lens of post-liberal human rights analysis. The argument can apply to many situations of forced evictions across Africa, Latin America, and the West itself.